Development and Characterization of Multi-Wavelength Fiber Laser Light Sources Based on Erbium and Brillouin Gain - Saharudin, Suhairi (2006)
This thesis presents the research works that has been carried out in the development and characterizations of light sources based on two gain medium, namely Erbium and Brillouin. The laser gain medium used in the research work is in the form of optical fiber rather than bulk piece of doped crystal or glass. The physical structure of the gain medium makes it easy to be spliced with other optical components in the Fiber laser configurations. The Brillouin gain comes from a standard single mode fiber used in the optical fiber communication system. The aim of the research work is to investigate various techniques in Fiber laser that allow the generation of multiple laser output (or multi-wavelength) from a single light source unit. The techniques differ from each other in the wavelength selection mechanism and the gain medium used in the configurations.